2022
DOI: 10.3389/fcimb.2022.919414
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Occurrence and 30-Day Mortality for Co-Infection of Carbapenem-Resistant Klebsiella pneumoniae and Carbapenem-Resistant Acinetobacter baumannii

Abstract: BackgroundThe phenomenon of co-infection with multiple carbapenem-resistant bacteria is growing, which pose a great challenge for infection control and treatment. This study aimed to analyze predictors of occurrence and 30-day mortality for carbapenem-resistant Klebsiella pneumoniae and carbapenem-resistant Acinetobacter baumannii co-infection.MethodsFrom June 2018 to June 2021, clinical data of 103 patients co-infected with carbapenem-resistant Acinetobacter baumannii (CRAB) and carbapenem-resistant Klebsiell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although many researchers [40][41][42] have resorted to tigecycline, this broad-spectrum antibiotic, as the last effective therapeutic option in difficult-to-treat patients, especially those with MDR Acinetobacter infections, there is no antibiotic without side effects. Tigecycline is known for its hepatotoxicity, and there is a debate regarding its association with increased mortality rates [43][44][45][46][47]. Moreover, bacteria began to develop resistance against tigecycline [48].…”
Section: Discussionmentioning
confidence: 99%
“…Although many researchers [40][41][42] have resorted to tigecycline, this broad-spectrum antibiotic, as the last effective therapeutic option in difficult-to-treat patients, especially those with MDR Acinetobacter infections, there is no antibiotic without side effects. Tigecycline is known for its hepatotoxicity, and there is a debate regarding its association with increased mortality rates [43][44][45][46][47]. Moreover, bacteria began to develop resistance against tigecycline [48].…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae and A. baumannii have a mutually beneficial relationship, protecting and feeding each other to promote their survival [ 28 ]. Plasmids carrying resistance genes can also be transferred between them [ 29 ]. Accordingly, we found that the coexistence of carbapenem-resistant A. baumannii was associated with CRKP infection.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, iucA, rmpA, rmpA2, iroB, and peg-344, were recently described as the most prevalent virulence genes in Taiwan (Liao et al, 2022), while genes ybt, iuc, and rmp were recently described as the most prevalent in China (Cienfuegos-Gallet et al, 2022). Co-infection of K. pneumoniae with other bacterial agents (i.e., Acinetobacter baumannii, P. aeruginosa, and E. coli, among other less frequent bacteria) has been documented and sized previously (Karakonstantis et al, 2022;Lv et al, 2022).…”
Section: Pathogen Factorsmentioning
confidence: 99%